2012
DOI: 10.1039/c2sm06960a
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous segregation of self-propelled particles with different motilities

Abstract: We study mixtures of self-propelled and passive rod-like particles in two dimensions using Brownian dynamics simulations. The simulations demonstrate that the two species spontaneously segregate to generate a rich array of dynamical domain structures whose properties depend on the propulsion velocity, density, and composition. In addition to presenting phase diagrams as a function of the system parameters, we investigate the mechanisms driving segregation. We show that the difference in collision frequencies b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
201
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(220 citation statements)
references
References 71 publications
17
201
2
Order By: Relevance
“…We observe that due to the small noise, the particles tend to form large clusters with velocity magnitude , except at domain edges where the local density takes smaller values. There is also some evidence of a phase separation between "slow" and "fast" SPP, in analogy with the results found in [34] for a mixture of SPP with different speeds. Unlike the domains found in the shear simulations, though, the slow and fast clusters later on merge into a giant cluster of slow particles and some isolated clusters of faster 0 .…”
Section: Density-dependent Movementsupporting
confidence: 65%
“…We observe that due to the small noise, the particles tend to form large clusters with velocity magnitude , except at domain edges where the local density takes smaller values. There is also some evidence of a phase separation between "slow" and "fast" SPP, in analogy with the results found in [34] for a mixture of SPP with different speeds. Unlike the domains found in the shear simulations, though, the slow and fast clusters later on merge into a giant cluster of slow particles and some isolated clusters of faster 0 .…”
Section: Density-dependent Movementsupporting
confidence: 65%
“…Here the passive particles would play the role of the solvent and optical tweezers [30], "electric bottles" [32] or suitable microfluidic devices [33] could be used for selective confinement. Suspensions of active colloids are currently attracting much attention for their novel phase behavior [34][35][36][37][38][39][40][41], and active-passive mixtures should show even richer physics [42]. Osmotic effects are very likely to play a key role in the behavior of such systems.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, models of self-propelled particle systems and active fluids suggest that behavioral parameters of individuals are often critical to collective dynamics [11,15,16,18]. For example, Chaté et al studied the role of noise in active nematic systems and found that correlation length diverges (i.e., quasi-long-range order emerges) below a critical noise strength [89]; McCandlish et al and Hinz et al modeled mixtures of self-propelled particles with different motilities, and found that such systems displayed phase separation [90] and could give rise to dynamical phases [91]; Nagai et al found that selfpropelled particles with memory of past trajectories (i.e., with underdamped angular dynamics) displayed a rich variety of phases not observed in systems without memory, such as vortex lattices and active foam [92]. To understand the connections between individual cell's behavior and the emergent collective behavior, and to verify model predictions in experimental systems of bacterial collective motion, it is desirable to control the behavior of individual cells as well as their physicochemical environment.…”
Section: Controlling Bacterial Collective Motion In Two Dimensions: Amentioning
confidence: 99%